CSISG fieldwork methodology whitepaper - Institute of Service Excellence, SMU (Institutional Knowledge at Singapore Management University, 2020)
Comparisons of Results and Respondent Demographic Profiles between Interviewer Administered Face-to-face Survey and Respondent Self-administered Online Survey for the Customer Satisfaction Index of Singapore (CSISG)